A handbook of ancient religions - Hinnells, John R. (Gale virtual reference library, 2007)
Provides a scholarly account of ancient cultures around the world, from China to India, the Middle East, Egypt, Europe, and the Americas. It outlines the history of the different societies so their religion and culture can be understood in context.